Annual reviews of computational physics VI - Stauffer, Dietrich (Singapore World Scientific, 1999)
The sixth volume of the series covers topics ranging from the generation of good random numbers to statistical physics, quantum mechanics, quantum computers and polymers, to protein folding and immunology simulations.
Includes references and index
Keywords: Cơ bản